Urban landscape changes in Kampung Baru, Kuala Lumpur, from 1969 to 2004 as observed on maps. - Hashim, Nor Rasidah; Mohd Yaacob, Naziaty (2011)
Kuala Lumpur has undergone massive development since Malaysia gained its independence in 1957. Our map analysis describes how Kampung Baru, which is a little pocket of traditional Kuala Lumpur, has changed in two different post-Independence periods: 1. The mid-20th century (1969) and 2. The early 21st century (2004). The maps used are published by the Department of Survey and Mapping Malaysia at the scale of 1:50,000 for the 1969 map and at 1:10,000 for the 2004 map. Our observation shows that in both maps, Kampung Baru is having a historical-spatial relationship with Sungai Klang but the importance of the river to the people has changed over time as does the surrounding areas. The spatial patterns of Kampung Baru at the map scales appeared to be relatively regular, and the natural topography in and around Kampung Baru is clearly shown to be impacted by anthropogenic activities that have been driven by rapid population growth. This map-based analysis adds to our understanding about the on-going process of urban development in Kampung Baru.